Comparative Study of Swelling Pressure in Expansive Soils considering Different Initial Water Contents and BOFS Stabilization. (2nd February 2023) - Keskin, İnan and Salimi, Mahdi and Ateyşen, Eylem Özge and Kahraman, Selman and Vakili, Amir Hossein
Abstract : In terms of geotechnical engineering, swelling soils are among the most important soil groups whose characteristics should be determined in detail before design studies. These types of soils cause significant damage to engineering structures. For this reason, it is expected that the swelling behavior of the soils will be known in advance to minimize the damage that may occur in the structures. Within the scope of this study, the swelling pressures of bentonite clay with 10 different water content were determined by keeping all conditions the same to reveal the effect of water content on soil swelling behavior. In this context, bentonite-type (montmorillonite content) clay, which has a very swelling property when it comes in contact with water, was used in the experiments. The fixed volume swelling pressure test method was used in the experiments and all samples were compressed at the same rate and placed in the swelling test device. In all samples left to swell with pure water, measurements were made for 10 days and the effects of swelling pressures on the initial water content were discussed. Thereafter, another swelling soil was stabilized using basic oxygen furnace slag (BOFS) during different curing times, and after performing the swelling pressure test, the results were compared with the findings obtained from different initial water contents. According to the results, while the swelling pressures increase in the regions close to optimum water content, significant decreases are observed in swelling pressure values in wetter and drier regions than in optimum water content. Finally, the results indicated that the application of BOFS, albeit small, after the proper curing time can significantly affect the swelling behavior of bentonite, even more than changing the initial water content.